PENGARUH VARIABEL HARGA DAN RESPONSIF TERHADAP KEPUASAN TAMU HOTEL - Alwin Teniro; Zainuddin - Zainudin (Universitas Teuku Umar, 2022)
The purpose of this research is: To find out the Effect of Price and Responsiveness to guest satisfaction at Mahara Hotel, Central Aceh Regency. Data analysis used is qualitative and quantitative, qualitative analysis tool in the form of categorization and quantitative analysis tool in the form of coefficient of determination, t test, F test of respondents as many as 73 people. The results of the study are known that partially the price has a significant and positive effect on the diss whole of mahara hotel guests, partially that responsiveness has a positive and significant effect on satisfaction in mahara hotel guests, simultaneously that the variable price and responsiveness affect satisfaction in hotel guests Mahara the relationship between independent variables to dependent variables is strong, the satisfaction of mahara hotel guests can be influenced by price variables and responsiveness. That's 55.4%. And the rest was not observed in this research mode.